(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acute respiratory viral infections (ARVI) are among the most common infectious diseases worldwide, with more than one billion cases reported annually. Viral infection affects not only the epithelial layer but also significantly alters the composition and functional stability of the nasopharyngeal microbiota. Studies show that during ARVI, opportunistic bacteria such as Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis proliferate markedly, while beneficial commensal populations of Corynebacterium and Dolosigranulum decrease. These changes determine disease severity, the risk of bacterial superinfection, the need for antibiotic therapy, and the quality of the immune response. This article analyzes the dynamic changes of the nasopharyngeal microbiota during ARVI, their clinical significance as biomarkers, and their role in personalized therapy.